The Structure and Performance of Ethiopian Banking Industry - Yirga, Netsanet (International Journal For Research In Business, Management And Accounting, 2017)
This study is aimed at evaluating the performance and structure of Ethiopian banking sector. The deposit, capital and loan performance of all commercial banks in Ethiopia from 2003/4 to 2014/15 were considered in order to investigate the structure and performance of the sector. A comparative analysis has been made to evaluate the position of public and private owned banks. Furthermore, HHI technique is used to evaluate the competition level of the industry. The performance of the sector in relation with deposit, capital and loan has dramatically increased in the periods considered. the public banks has strong domination in all the measures taken in to account with the domination of CBE which owned more than half of the market share in all aspects. Due to this fact the HHI indicated that the banking sector of Ethiopia is highly concentrated in relation with deposit, loan and capital implying that the competition level in the sector is very low.